13.4k views
2 votes
Solve 4(2x - 9) = 3x + 4

User Bjackfly
by
6.4k points

2 Answers

2 votes

Answer:

x = 8

Explanation:

First, you distribute

4(2x)+4(-9)=3x+4

8x - 36 = 3x + 4

Subtract 3x from both sides

(8x - 3x) - 36 = (3x - 3x) + 4

5x - 36 = 4

Then add 36 to both sides

5x (-36 + 36) = (4 + 36)

5x = 40

Then divide 5 from both sides

x = 8

------------------------

Hopefully this is correct, sorry if it isn't

User HavelTheGreat
by
5.8k points
3 votes
8x - 36 = 3x + 4
5x = 40
x = 8
User HargrimmTheBleak
by
6.3k points